The Police Investigators’ Strategy in Handling Narcotics Crime in the Jurisdiction of Ngawi Police Resort - Faisal Ferdiansyah; Sirajjudin; Krista Yitawati (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Abstract Introduction to the Problem: The issue of narcotics continues to escalate and poses a serious threat within the jurisdiction of Ngawi, both in terms of circulation and abuse. Purpose/Study Objectives: This study aims to analyze the role, challenges, and strategies implemented by investigators at the Ngawi Resort Police (Polres Ngawi) in combating narcotics-related crimes. Design/Methodology/Approach: This research employs a juridical-empirical method with a qualitative approach. Data is collected through direct interviews with investigators from the Narcotics Unit of the Ngawi Resort Police (Satresnarkoba Polres Ngawi), field observations, and documentation of narcotics cases from 2023 to 2025. Findings: In carrying out their duties, investigators employ preventive, preemptive, and repressive approaches. However, they face various challenges, such as limited personnel, insufficient facilities and infrastructure, and low public participation. To address these issues, strategies such as enhancing human resource capacity, fostering intersectoral cooperation, and strengthening outreach and rehabilitation programs are implemented. The research findings indicate that the success of narcotics control requires strong synergy between law enforcement agencies, the government, and the community.